PENDIDIKAN AGAMA ISLAM ZAMAN MEKAH AWAL (Di antara Dua Peradaban Jahiliyah Dan Romawi/Persi) - M. Hasyim Syamhudi (Universitas Nurul Jadid, 2016)
Historically, Mecca, which lies on Arabian Peninsula, could not be separated with the development of Islamic education. This is not only due to the city as the birth place of Mohammad the prophet of Allah SWT, but also where the Islamic education started. Islamic education in early Mecca developed under the two biggest civilizations: Roman and Persian. Meanwhile, it was also faced the Jahiliya regime that strongly rooted in the Arabian Mecca communities. The strength of Mecca inhabitants in holding their pagan belief made the two civilizations have no significant influences in the area. Therefore, Mecca was politically and culturally free of any other influences. Moreover, Ibnu Khadun, as cited by A. Sjalabi, once said that Arabian Peninsula was never entered by foreigners. That is why the language is still pure. Geographically, Mecca is located in the west side of the Saudi Arabian Emperor, surrounded by mountains of 300 meters above sea level. Its terrace, made Mecca unfavorable for foreigners and also for Roman and Persian to occupy it as their colony. The complexities of Mecca make it suitable for Muhammad SAW to do the mission of spreading Islam in the region.